Fauna helmintológica de ovinos provenientes da microrregião de Jaboticabal, estado de São Paulo, Brasil - Maciel, Willian Giquelin [UNESP]; Felippelli, Gustavo [UNESP]; Lopes, Welber Daniel Zanetti [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Cruz, Breno Cayeiro [UNESP]; dos Santos, Thais Rabelo [UNESP]; Buzzulini, Carolina [UNESP]; Favero, Flavia [UNESP]; Gomes, Lucas Costa [UNESP]; de Oliveira, Gilson Pereira [UNESP]; da Costa, Alvimar José [UNESP]; de Matos, Lucas Vinícius Shigaki [UNESP] (FapUNIFESP (SciELO), 2014)
This study evaluated the prevalence and counting parasitism of different species of helminths of sheep from the micro-region of Jaboticabal of São Paulo state. For this, 66 animals naturally infected, four to 36 months of age, raised in pasture, were selected. The results of necropsy revealed the presence of seven genera and 12 species with the following prevalence and mean count: Haemonchus contortus: 100.0% (2947.2); Trichostrongylus colubriformis: 90.9% (3048.8); Cooperia curticei: 56.0% (256.5); Oesophagostomum columbianum: 48.4% (36.0); Cooperia punctata: 30.3% (94.5); Trichostrongylus axei: 22.7% (26.5); Strongyloides papillosusi: 19.6% (83.0), Haemonchus contortus (L4): 7.5% (17.2), Cooperia pectinatai: 10.6% (12.9), Trichuris ovis: 10.6 % (0.6); Cooperia spatulata 4.5% (0.3); Capillaria bovis: 4.5% (0.1). The mean parasitism of helminthswas 6524.7 per animal. Haemonchus contortus (adults and L4) and Trichostrongylus colubriformis corresponded to 45.4% and 46.7% of the average worm burden totally, respectively. Based in the results obtained in this study, can be concluded that the two most abundant species of helminths and important, the micro-region of Jaboticabal are Trichostrongylus colubriformis and Haemonchus contortus, and these two species amounted to 92.1% of the distribution percentage of helminths collected from all animals. These results demonstrate the importance of conducting a counts of eggs per gram of feces (EPG) in the herds of this region when FAMACHA is used on a particular property, since this method control does not allow to diagnostic the damage/clinical signs in animals infected by T. colubriformis, because this specie does not have hematophagism habit on animals.
Helminth fauna of sheep from the micro region of Jaboticabal, São Paulo State, Brazil
Keywords: FAMACHA; Helminths; Nematode; Prevalence; Sheep